Sentence of the Bogota river (2018)
This essay is articulated to the Environmental Management research line of the Specialization in Finance and Public Administration of the New Granada Military University and aims to evaluate the impact of the orders issued by the Sentence of the Río Bogotá, as opposed to the territorial entities and the fulfillment of the obligations by these acquired, since in said Judgment planning and management instances are determined, which will allow to advance the actions of the territorial entities in the process of ecological recovery of the Bogotá River Basin.